THE INTRICATE RELATIONSHIP BETWEEN PARENTS, TEACHERS AND MEDIA IN THEIR CONTEXT OF NATION-BUILDING - Olumuji, Emmanuel (UI Scholars Hub, 2025)
This study examines the intricate relationship between parents, teachers, and media in the context of nation-building, emphasizing their collective role in shaping societal values and fostering holistic development. Drawing insights from scholarly literature and empirical studies, the study considers the influence of parents, teachers, and media on child development, moral education, and civic engagement. The study underscores the pivotal role of educators in instilling moral values, critical thinking skills, and civic responsibility among students, thereby contributing significantly to the development of a nation's human capital. Moreover, the study highlights the media's potential as a catalyst for social change, advocating for media literacy initiatives and responsible media engagement to promote informed citizenship. Through collaborative efforts and policy support, stakeholders can leverage the synergies between parents, teachers, and media to nurture resilient communities and build a prosperous future for generations to come.